Comparative Effects of Ancymidol and Its Analogs on Growth of Peas and Ent-Kaurene Oxidation in Cell-Free Extracts of Immature Marah macrocarpus Endosperm - Coolbaugh, Ronald C. (1982)
The plant growth retardant α-cyclopropyl-α-(4-methyoxyphenyl)-5-pyrimidine methyl alcohol (ancymidol) and a series of analogs of this substance in which one or more of the substituents were varied were tested for their comparative biological activity. The compounds were tested as inhibitors of internode elongation in peas and as inhibitors of the oxidation of ent-kaurene catalyzed by microsomal preparations from the liquid endosperm of Marah macrocarpus seeds. The relative effectiveness of a substance was generally the same as an inhibitor of the two processes. Ancymidol was the most effective. Substitution of the alcohol group of ancymidol by either methoxy or hydrogen groups reduced the activity only slightly. Substitution of the cyclopropyl group by an isopropyl moiety also had little effect on the activity. However, substitution of the cyclopropyl group with a phenyl or other aryl substituent greatly reduced the effectiveness of the analog as an inhibitor. Replacement of the 4-methoxyphenyl substituent with a similar substituent such as 4-chlorophenyl had little effect on activity, but replacement with a 2-methoxyphenyl group greatly reduced activity. Analogs in which the pyrimidyl moiety of ancymidol was modified were inactive in whole plants, but moderately active in the cell-free ent-kaurene oxidation system. The application of gibberellic acid can overcome the growth inhibitions due to treatment of the test plants with 10(−5)m or lower concentrations of the inhibitors. However, the inhibitory effects of 10(−4)m or higher concentrations of inhibitors on test plants were not overcome by the applications of exogenous gibberellic acid. These results support the idea that the effects of low concentrations of these substances on plant growth are primarily a consequence of their ability to inhibit ent-kaurene oxidation and gibberellin biosynthesis. Other modes of inhibition may operate at higher inhibitor concentrations.